General Anesthesia and Modified Rapid Sequence Induction for Emergency Cesarean Delivery in an Eclamptic Adolescent with Severe Thrombocytopenia - Yohannes Baptista Paskah Prasanto; Purwoko (HM Publisher, 2026)
Background: Eclampsia complicated by severe thrombocytopenia presents a critical anesthetic challenge, often representing an absolute contraindication to neuraxial anesthesia. When alternative approaches are mandated, General Anesthesia with Rapid Sequence Induction or a modified rapid sequence approach is crucial for high-risk obstetric emergencies. Case presentation: A 16-year-old primigravida at 35 weeks gestation presented with eclampsia, acute fetal distress, and severe thrombocytopenia. Initial vitals showed a blood pressure of 150/98 mmHg. Laboratory findings confirmed severe preeclampsia with a critical platelet count of 42,000/µL. An airway assessment revealed a Mallampati class II airway with mild pharyngolaryngeal edema. Due to the high risk of spinal epidural hematoma, neuraxial anesthesia was contraindicated. An emergency cesarean section was performed using a modified rapid sequence induction. Following preoxygenation, induction was achieved with fentanyl 100 µg, midazolam 3 mg, and propofol 100 mg. Due to institutional unavailability of rocuronium, atracurium 30 mg was utilized. After a 2.5-minute onset interval utilizing apneic oxygenation and continuous cricoid pressure, the patient was successfully intubated on the first attempt with a Macintosh size 3 blade. The intraoperative course was hemodynamically stable. Conclusion: A modified rapid sequence induction utilizing atracurium provides an effective alternative for airway control and physiological stability in eclamptic adolescents with coagulopathy, particularly in resource-limited settings where standard rapid-acting non-depolarizing agents are unavailable.